Tribological characterization of tungsten nitride coatings deposited by reactive magnetron sputtering - Polcar, T. (2007)
The structure, hardness, friction and wear of tungsten nitrides prepared by d.c. reactive magnetron sputtering were investigated. The coatings were deposited with different nitrogen to argon ratios; the total pressure was kept constant. The tribological tests were performed on a pin-on-disc tribometer in terrestrial atmosphere with 100Cr6 steel, Al2O3 and Si3N4 balls as sliding counter-bodies. The wear tracks, the ball-wear scars and the wear debris were analysed by scanning electron microscopy in order to characterize the dominant wear mechanisms.